Prevalence of ABO and Rh Blood Group Phenotypes Among Pregnant Women - Mabroukah Turfayah; Adham Alshuwayhidi; Soad Ajroud (African Journal of Advanced Pure and Applied Sciences, 2025)
Knowledge of the ABO and Rh blood group systems is essential to clinical practice. Maternal mortality and morbidity during childbirth remains a significant concern worldwide, with blood loss being the leading cause of death. Health care management during antenatal periods highly relies on the verification of maternal ABO and Rh blood. This is crucial to prevent complications outcomes, like hemolytic disease of newborns (HDN), postpartum hemorrhage, and miscarriage. Details on the prevalence of the ABO and Rh blood groups among pregnant women in Libya are lacking. The Objective of this research is to study the distribution pattern of the ABO and Rh blood groups among pregnant women in the city of Derna, north-eastern Libya. A retrospective, health records-based study was conducted at Al-Wahda Teaching Therapeutic Hospital, Derna from January 2020 to December 2023 and enrolled 5012 women at delivery. Blood samples were collected upon admission and ABO and Rh typing were performed using slide agglutination method. Descriptive statistical results were shown in frequency and percentage. The results revealed that group O positive was the most prevalent blood phenotype (32%), followed by A positive (29.5%), B positive (19.9%), AB positive (6.9%), O negative (4.6%), A negative (3.6%), B negative (2.3%) and AB negative (0.8%). The Conclusion of the study shed light on the prevalence of the ABO and Rh blood phenotypes on large scale basis. Our findings may provide a reliable database to help optimize blood reserves and ensure safe blood transfusion during pregnancy and delivery.